The preparation of electrospun fiber mats containing propolis Extract/CL-CMS for wound dressing and cytotoxicity, antimicrobial, anti-herpes simplex virus - Sutjarittangtham K. (American Scientific Publishers, 2015)
Copyright © 2015 American Scientific Publishers All rights reserved. Wound dressing has developed continuously over a period of time, start by simply acting to cover the wound. The modern bandage materials are containing various active compounds for beneficial to the healing of wounds and have many techniques for preparation. The electrospinning is one of the most important techniques for wound dressing preparation. In this research, we prepared the fiber mats containing propolis extract and cross-linked carboxymethyl starch (CL-CMS) by electrospinning. All samples were prepared in three layers, the top and the base layers are poly(vinyl alcohol) (PVA) fiber mat, the middle layer is poly(vinyl pirolidone) (PVP)/propolis or PVP/propolis/CL-CMS. The samples were separate two groups, one group containing various amount of propolis. The propolis was varied from 0% w/v,by 1% w/v, 3% w/v and 5% w/v. The morphology of samples were observed by SEM. It was found that, they were smooth and in the medium layer, the CL-CMS powders appeared. S. aureus, S. epidermidis, B. cereus, MRSA and P. aeruginosa were antibacterial tested by using disdiffusion method, at 5% w/v of the propolis was the maximum of the antibacterial activity. Cytotoxicity and antiviral activity were tested. The CD50 of the sample at 0% w/v of the propolis is 794.38 ± 0.00 μg/ml, when increased the propolis concentration the CD50was decrease.